A Concise Synthesis of 24,25-Dihydro-6-epi-Monanchosterol A - Taspinar, Ömer; Stojadinovic, Vladimir Kjartan; Neudörfl, Jörg-Martin; Schmalz, Hans-Günther (Synlett, 2021)
We report the first synthetic entry to a steroid with an unusual bicyclo[4.3.1]dec-3-en-10-one A/B ring substructure as a close structural analogue of the anti-inflammatory monanchosterols. Under optimized conditions, regioselective cis-dihydroxylation of the Δ5-double bond of 7-dehydrocholesterol and subsequent Criegee oxidation yields the corresponding 5,6-seco-steroid as a pure Z-isomer which upon treatment with K2CO3 in MeOH diastereoselectively affords 24,25-dihydro-6-epi-monanchosterol A through intramolecular aldol addition (cyclization). The developed three-step sequence proceeds in 17% overall yield without the need of any protecting group. The title compound was characterized by X-ray crystallography.
Keywords: steroids; natural products; intramolecular aldol addition; olefin cis-dihydroxylation; oxidative glycol cleavage